2001
DOI: 10.1063/1.1372185
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo studies of the structure and spectroscopy of NenOH (Ã 2Σ+, n=1–4) van der Waals complexes

Abstract: Adiabatic rigid-body diffusion Monte Carlo is used to study the structure and spectroscopy of complexes of OH(Ã 2Σ+) with several neon atoms. Although the potential energy surfaces for these systems have many low-lying minima, the ground state wave functions are localized in the global minimum. This trend is found to persist in the first few vibrationally excited states of Ne2OH/D. Low-lying vibrational states that are localized in the potential minimum that corresponds to the linear Ne–OH/D–Ne configuration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…While the energies obtained either from converged variational calculations that employ the full rotation-vibration Hamiltonian or from second-order perturbation theory will be independent of how the body-fixed axis system is defined, the contribution to A υ , B υ , and C υ from Coriolis terms in the Hamiltonian will depend sensitively on the choice of embedding of the body-fixed axis system. A common choice is an Eckart frame, , which has two advantages. First, it captures the rotational symmetry of the molecule and retains this symmetry when the molecule is in a totally symmetric vibrational state.…”
Section: Introductionmentioning
confidence: 99%
“…While the energies obtained either from converged variational calculations that employ the full rotation-vibration Hamiltonian or from second-order perturbation theory will be independent of how the body-fixed axis system is defined, the contribution to A υ , B υ , and C υ from Coriolis terms in the Hamiltonian will depend sensitively on the choice of embedding of the body-fixed axis system. A common choice is an Eckart frame, , which has two advantages. First, it captures the rotational symmetry of the molecule and retains this symmetry when the molecule is in a totally symmetric vibrational state.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of this approximation is minimized by embedding the body-fixed axis system using the Eckart conditions, which are constructed to eliminate the Coriolis coupling terms in the limit of small-amplitude vibrations. , Although Coriolis coupling cannot be completely eliminated in systems that undergo large-amplitude vibrational motions, in several recent DMC studies of fluxional molecules and clusters, including CH 5 + , we and others have shown Eckart embedding to be a reasonable approach for obtaining vibrationally averaged rotational constants. Interestingly, these rotational constants were shown to be independent of the details of how the Eckart frame was defined, and in the case of symmetric top molecules two of the vibrationally averaged rotational constants were equal to within their statistical uncertainties. ,,,, Eckart embedding also has been shown to produce a sufficient reduction in rotation–vibration coupling to allow rotationally excited states of floppy molecules to be described using fixed-node DMC with the nodes placed in the Euler angles that relate the space-fixed and Eckart frames. , …”
Section: Theorymentioning
confidence: 98%
“…Analysis of these wave functions can often provide important physical insights into how the excitation affects the molecular structure and nuclear dynamics of the system. In a number of previous calculations we have demonstrated that fixed-node DMC can be effectively used to study the vibrationally and rotationally excited states of highly fluxional molecules and clusters. , Despite their success, these fixed-node DMC studies were very computationally demanding, with a separate set of statistically independent DMC simulations required for each nodal region of each excited state considered in the studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations